Specificity of affective and autonomic symptoms of depression in Parkinson's disease. - Starkstein, S E (1990)
Previous investigators have suggested that numerous symptoms used to diagnose depression, such as sleep or appetite disturbance, are non-specific in medically ill patients, and alternative diagnostic criteria should be developed. In the study this hypothesis was tested in Parkinson's disease (PD) by comparing patients with PD who reported a depressive mood with patients having PD but without a depressive mood. Depressed patients showed a significantly higher frequency of both autonomic and affective symptoms of depression. Depressed patients with PD reported a significantly higher frequency of worrying, brooding, loss of interest, hopelessness, suicidal tendencies, social withdrawal, self-depreciation, ideas of reference, anxiety symptoms, loss of appetite, initial and middle insomnia, and loss of libido when compared with non-depressed patients. No significant between-group differences, however, were observed in the frequency of anergia, motor retardation, and early morning awakening.